The Relationship between Consumer Characteristics (Demographic Characteristics and Personality Traits) and SST Adoption in Multiple Service Industries in Saudi Arabia (Global Journal of Management and Business Research, 2015)
Abstract not found
Keywords: demographic characteristics; personality traits; SST adoption and service industries in Saudi arabia